The Morton Manuscript: ’ancient inscriptions on stones found in Scotland’ - Keppie, Lawrence (Proceedings of the Society of Antiquaries of Scotland, 2015)
An eight-page manuscript, presented to the Society of Antiquaries of Scotland in 1827 and, until recently, considered lost, lists nine Roman and four medieval inscriptions, of which four are otherwise unknown. This paper discusses the sources used in the compilation of the manuscript, which is traditionally ascribed to James Douglas, 14th earl of Morton (1702–68). The conclusion reached here is that much of the information which it contains was assembled in the mid-17th century and collated into its present form much later, perhaps in the early 18th century.